2021
DOI: 10.1097/pas.0000000000001834
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of B-Cell Lymphomas to CAR T-Cell Therapy Is Associated With Genomic Tumor Changes Which Can Result in Transdifferentiation

Abstract: Despite the impressive efficacy of chimeric antigen receptor (CAR) T-cell therapy (CART) in B-cell non-Hodgkin lymphomas, durable responses are uncommon. The histopathologic and molecular features associated with treatment failure are still largely unknown. Therefore, we have analyzed 19 sequential tumor samples from 9 patients, prior anti-CD19 CART (pre-CART) and at relapse (post-CART), using immunohistochemistry, fluorescence in situ hybridization, array comparative genomic hybridization, next-generation DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 48 publications
(110 reference statements)
0
11
0
Order By: Relevance
“…[15][16][17][18][19] CAR T-cell product properties, such as kinetics and dose, can also be taken into account, 20 along with tumoral intrinsic factors. [21][22][23] Chow et al previously reported a poor outcome in 61 patients presenting progression or relapse after CAR T-cell treatment. 24 The DESCAR-T registry offers a unique opportunity to gather data about a large European cohort.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18][19] CAR T-cell product properties, such as kinetics and dose, can also be taken into account, 20 along with tumoral intrinsic factors. [21][22][23] Chow et al previously reported a poor outcome in 61 patients presenting progression or relapse after CAR T-cell treatment. 24 The DESCAR-T registry offers a unique opportunity to gather data about a large European cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Disease relapse can occur by 12 months after infusion of CAR-T cells in up to 50% of patients [197]. Relapse connected with CD19 antigen loss is also observed in the case of NHLs but is less frequent than in ALL [198].…”
Section: Car-t Cellsmentioning
confidence: 99%
“…The broad analysis of samples from patients with lymphomas (mainly DLBCL) before and after CD19 CAR-T therapy displayed a tremendous phenotypic shift in tumor cells after CAR-T infusion. These genomic changes included downregulated expression of B cell markers (CD19, CD20, CD22, CD79a), an increased methylation profile, and mutations affecting immune suppressive mechanisms, such as the PI3K pathway [ 116 ].…”
Section: Mechanisms Of Resistance To the Cd19 Car-t Therapy In B Cell...mentioning
confidence: 99%